Analisis Potensi Ekonomi Kreatif Berbasis Kearifan Lokal di Kampung Soaib Distrik Kemtuk, Kabupaten Jayapura - Elza Natalia; Lazarus Ramandei; Sudiro Sudiro (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
This study aims to analyze the potential of local wisdom-based creative economy in Soaib Village, Kemtuk District, Jayapura Regency. Soaib Village has cultural wealth and abundant natural resources, including organic cocoa and orchids, which make it potential to be developed into a sustainable creative economy sector. This research used a descriptive qualitative approach with data collection through observation, interviews, and documentation. Data analysis was conducted using the SWOT method, explanatory analysis, and Geographic Information System (GIS) to map the potential of existing resources. The results showed that organic cocoa and orchids are leading sectors that can be the driving force of the local economy. However, there are significant challenges, such as limited infrastructure, lack of technical training, cocoa pests, and limited market access. Support from organizations such as WWF in providing training and mentoring has had a positive impact, especially in improving community skills related to forest product management and orchid cultivation. The SWOT analysis revealed several key factors: (1) strengths in the form of natural resources and active community participation; (2) weaknesses in the form of lack of infrastructure and capital; (3) opportunities in the form of global demand for organic products and government support; and (4) threats in the form of climate change and competition from other regions. With more structured and inclusive management, this potential can be maximized to support sustainable economic development. This research emphasizes the importance of local wisdom as a foundation in creative economic development, while maintaining environmental sustainability. The resulting strategic recommendations include improving infrastructure, strengthening technical training, strengthening local institutions, and promoting awareness about the importance of sustainability. With these steps, Soaib Village is expected to become an example of successful management of local wisdom-based creative economy that can be replicated in other areas.